Geography and Environment : Trajectories and Trends of Geosystems Research in the State of Sao Paulo - das Neves, Carlos Eduardo [UNESP] (2017)
Geosystems analysis is of great importance in geographical research, considering the necessity of understanding the relationships between society and nature. In this scenario, we sought to understand the development of geographical research on geosystems in the state of Sao Paulo, Brazil in the period between 1971 and 2011. In view of that, we carried out theoretical and methodological analyses of master's theses and doctoral dissertations submitted to UNESP - Sao Paulo State University (in two cities: Rio Claro and Presidente Prudente), UNICAMP - State University of Campinas, and USP - University of Sao Paulo, adapting Gamboa's (1987). We used theoretical and methodological framework, digital database creation for bibliometric analysis, in addition to other historical-documental and statistical calculations and geoprocessing. The present research aims to systematize scientific contributions dispersed in time, assisting in the understanding of trends and trajectories of geosystems research and its correlation with and importance to the development of environmental studies in the Brazilian geographical science.